Transforming Economic Systems: The Case of Poland With the Cooperation of Feliks Gradalski - Kremer, Manfred; Weber, Marion (Contributions to Economics, 1992)
This book deals with the transformation of the Polish centrally-planned system to a western-type market system. Poland represents the most interesting case to study as it runs an unprecedentedly radical and fast course of reform. The book provides insights in the theoretical foundations of the transformation of an economic system as well as a critical assessment of first experiences in Poland. As the authors develop theoretical approaches as well as study the empirical situation, thebook offers valuable insights both to the reader who is rather theoreticallyinterested and to a pragmatically orientated audience. One of the main features of the book is the broad variety of the subjects chosen for analysis and of the respective approaches taken by the authors who mostly specialize in the fields they worked on for this book